Antioxidant rich nutraceutical formulation. - Ismail, Maznah (2011)

(untitled)
The present invention relates to antioxidants rich composition with potent physiological effects and enhanced bioavailability. This composition is a mixture of three antioxidants which are tocopherols, tocotrienols and gamma oryzanol. The fatty acids composition of the oily phase used in this composition is either rice bran oil extracted by organic solvent or supercritical fluid extraction or a blend of rice bran oil and palm oil. This formulation has a balanced ratio of saturated fatty acids to polyunsaturated and monounsaturated. Antioxidants content as well as fatty acids composition of this formulation have synergistic effect in cholesterol lowering effect, reducing lipid peroxidation, improve antioxidant status and reducing the risk of coronary heart disease.